GPi DBS treatment outcome in children with monogenic dystonia: a case series and review of the literature - Chudy, Darko; Raguž, Marina; Vuletić, Vladimira; Rački, Valentino; Papić, Eliša; Nenadić Baranašić, Nataša; Barišić, Nina (Frontiers in Neurology, 2023)
Introduction: Dystonia is the third most common pediatric movement disorder, and is often difficult to treat. Deep brain stimulation (DBS) of the internal pallidum (GPi) has been demonstrated as a safe and effective treatment for genetic dystonia in adolescents and adults. The results of DBS in children are limited to individual cases or case series, although is proven to be effective procedure in carefully selected pediatric cohorts. The aim of our study was to present treatment outcome of pediatric patients at the age 7-9 years with disabling monogenic isolated generalized DYT6-THAP 1 and DYT 28- KMT2B dystonia after bilateral GPi-DBS. Patients and Results: We present three boys at the age <10 years; two siblings with disabling generalized DYT6 -THAP1 dystonia and a boy with monogenic- complex DYT28-KMT2B. Dystonia onset was between age 3 and 6. Significantly disabled children were mostly depended on their parents. Pharmacotherapy was inefficient and patients underwent bilateral GPi DBS. Clinical signs of dystonia improved significantly in the first month after the implantation and continues to maintain gained motor functions and improving during further follow up. These patients are ambulant without support and included in everyday activities. In all patients Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) presented with significantly lower values indicating >25% improvement during first 15 months. However decline occurred both in speech and in upper limbs functions manifesting with bradylalia, bradykinesia and dysphonia which decreased on treatment with trihexyphenidyl. Conclusion: Although the number of reported patients with monogenic dystonia especially DYT-6 treated with DBS is still scarce, DBS should be considered as efficient treatment approach in children for pharmacoresistent, especially with generalized monogenic dystonia and to prevent severe and disabling symptoms decreasing the quality of life including emotional and social aspects. Still, the patients require individual approach and parents should be properly informed about expected and possible outcomes including relapses and impairments, beside DBS responsiveness and related improvements. Furthermore, early genetic diagnosis and providing appropriate treatment, including DBS are mandatory to prevent severe neurologic impairments.